The relationship between the Normalized Difference Vegetation Index and drought indices in the South Central United States - Bushra, Nazla; Rohli, Robert V.; Lam, Nina S. N.; Zou, Lei; Mostafiz, Rubayet Bin; Mihunov, Volodymyr (Natural Hazards, 2019)
Drought indices are useful for quantifying drought severity and have shown mixed success as an indicator of drought damage and biophysical dryness. While spatial downscaling of drought indicators from the climate divisional level to the county level has been conducted successfully in previous work, little research to date has attempted to “upscale” remotely sensed biophysical indicators to match the downscaled drought indices. This upscaling is important because drought damage and indices are often reported at a coarser scale than the biophysical indicators provide. This research upscales National Oceanic and Atmospheric Administration’s Advanced Very High Resolution Radiometer sensor-acquired Normalized Difference Vegetation Index (NDVI) data to produce a county-level biophysical drought index, for a five-state region of the South Central United States. The county-level NDVI is then correlated with the downscaled drought indices for assessing the degree to which the biophysical data match well-documented drought indicators. Results suggest that the Palmer Drought Severity Index and Palmer Hydrologic Drought Index are effective indicators of biophysical drought in much of the arid western part of the study area and in larger swaths of the study area in summer. In nearly all cases except for autumn months, correlations are weakest in the ecotones, with significant negative correlations in the humid eastern part of the study area. Results generally corroborate the findings of recent research that correlations between drought indices and biophysical drought vary spatially. As long-lead climate forecasts continue to improve, these results can assist environmental planners in preparing for the impacts of drought.
Keywords: Drought; Normalized Difference Vegetation Index; Palmer Drought Severity Index; Palmer Hydrologic Drought Index; South Central United States; Statistical upscaling